2004
DOI: 10.1111/j.1600-0846.2004.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with mild inflammatory catamenial acne

Abstract: Background: Acne is a multifactorial disease exhibiting distinct clinical presentations. Among them, the catamenial type is a matter of concern for young women. Some oral contraceptives may help without, however, clearing the skin condition. Aim:The present open study aimed at evaluating the effect of overnight applications of a paste made of petrolatum, 15% zinc oxide and 0.25% miconazole nitrate. Method: The split-face trial was conducted in 35 women. A non-medicated cream was used as control. Clinical evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The present fi ndings may explain in part the benefi cial effect of a miconazole nitrate paste on diaper dermatitis [25,26] and infl ammatory acne [27,28] . Indeed, skin capacitance imaging shows the close correspondence between the skin areas affected by infl ammation and altered barrier function in acne [36] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present fi ndings may explain in part the benefi cial effect of a miconazole nitrate paste on diaper dermatitis [25,26] and infl ammatory acne [27,28] . Indeed, skin capacitance imaging shows the close correspondence between the skin areas affected by infl ammation and altered barrier function in acne [36] .…”
Section: Discussionmentioning
confidence: 97%
“…Other topical formulations and some ions can help in correcting the excess of TEWL after damaging the SC [3,[19][20][21][22][23][24] . Previous studies have reported a benefi cial effect of a miconazole nitrate-containing paste in some infl ammatory dermatoses, even when fungal intervention did not appear to be involved [25][26][27][28] . We thus suspected that miconazole nitrate could have some biological effect other than its acknowledged antimicrobial effect.…”
mentioning
confidence: 99%
“…Comparative reflectance colorimetric assessments were performed on the photographs using a Visi‐Chroma® VC‐100 (Biophotonics, Lessines, Belgium). This computer‐assisted device allows to measure colours on very small and delimited areas defined by the observer 19,20 . Measurements were performed in the CIELAB system with L*a*b* notifications 21 .…”
Section: Methodsmentioning
confidence: 99%
“…A series of topical agents are usually effective for controlling catamenial acne [9]. In addition, suppression of both ovulation and postovulatory rises in progesterone levels is effective.…”
Section: Premenstrual Syndromementioning
confidence: 99%